Aerodynamic Study of a Single Groove on The Upper and Lower Surfaces of an Airfoil at Low Angles of Attack - AZMAN, MUHAMMAD AIDEED; Yaakub, Mohd Fauzi; Abdullah, Esmail; Wan Nawang, Wan Muhammad Aqil (Progress in Aerospace and Aviation Technology, 2025)
This project investigates the aerodynamic effects of introducing a single groove on both the upper and lower surfaces of a NACA 0012 airfoil at low angles of attack, ranging from 0° to 10°. Each simulation features two grooves, one on the upper surface and one on the lower surface, to evaluate their combined influence on lift and drag performance. The objective is to determine whether passive flow control via surface grooves can enhance aerodynamic efficiency in low-speed conditions. The study was conducted using computational fluid dynamics (CFD) simulations in ANSYS Fluent. Several groove configurations were analyzed, including parallel grooves at 0.20C, 0.25C, and 0.30C, as well as fixed upper grooves at 0.25C and 0.30C combined with variable lower groove positions at 0.25C to 0.40C. A mesh independence test and validation against experimental data were performed to ensure simulation accuracy. A groove diameter of 1.0 cm was selected based on its favorable aerodynamic performance across the tested angles of attack. Results indicate that the configuration with a fixed upper groove at 0.25C and a lower groove at 0.40C yields the most significant lift improvement and slight drag reduction compared to the baseline airfoil. The study demonstrates that using two grooves in a dual-surface configuration can effectively delay flow separation and enhance the lift-to-drag ratio. These findings support the advancement of passive aerodynamic control strategies in low-speed airfoil applications.